Walking away from back pain: one step at a time – a community-based randomised controlled trial - Milosavljevic, Stephan (BMC Public Health, 2015)
BACKGROUND: Low back pain is highly prevalent and a significant public health burden in Western society. Feasibility studies suggest personalised pedometer-driven walking is an acceptable and effective motivating tool in the management of chronic low back pain (CLBP ≥ 12 weeks). The proposed study will investigate pedometer-driven walking as a low cost, easily accessible, and sustainable means of physical activity to improve disability and clinical outcomes for people with CLBP in Saskatchewan, Canada. METHODS/DESIGN: A fully-powered single-blinded randomised controlled trial will compare back care advice and education with back care advice and education followed by a 12-week pedometer-driven walking programme in adults with CLBP. Adults with self-reported CLBP will be recruited from the community and screened for elibility. Two-hundred participants will be randomly allocated to one of two intervention groups. All participants will receive a single back care advice and education session with a physiotherapist. Participants in the walking group will also receive a physiotherapist-facilitated pedometer based walking programme. The physiotherapist will facilitate the participant to monitor and progress the walking programme, by phone, on a weekly basis over 10 weeks following two face-to-face sessions. Outcome measures of self-reported disability, physical activity, participants’ low back pain beliefs/perceptions, quality of life and direct/indirect cost estimates will be gathered at baseline, three months, six months, and 12 months by a different physiotherapist blinded to group allocation. Following intervention, focus groups will be used to explore participants’ thoughts and experiences of pedometer-driven walking as a management tool for CLBP. DISCUSSION: This paper describes the design of a community-based RCT to determine the effectiveness of a pedometer-driven walking programme in the management of CLBP. TRIAL REGISTRATION: United States National Institutes of Health Clinical Trails registry (http://ClinicalTrails.gov/) No. NCT02284958. Registered on 27(th) October 2014).